Project 1A: Graphic cultural poster / Anis Zulfah Zulkifli - Zulkifli, Anis Zulfah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The concept is the culture of Iban tribe, emphasizing specifically on their tattoos. The ritual and the process of tattoing are intrepreted in the visualisation of this poster. The Ibans believe that tattoos have mystical powers. Iban headhunters have scorpion tattoo on their body as a symbol of protection from malevolent spirits during battlefield.